Low-frequency electrical stimulation increases muscle strength and improves blood supply in patients with chronic heart failure - Dobšák, Petr; Nováková, Marie; Siegelová, Jarmila; Fišer, Bohumil; Vítovec, Jiří; Nagasaka, M; Kohzuki, M; Yambe, T; Nitta, S; Eicher, J.C; Wolf, J.E; Imachi, K (Circulation journal, 2006)
BACKGROUND: This study was designed to evaluate the effects of low-frequency electrical stimulation (LFES) on muscle strength and blood flow in patients with advanced chronic heart failure (CHF). METHODS AND RESULTS: Patients with CHF (n=15; age 56.5 +/- 5.2 years; New York Heart Association III - IV; ejection fraction 18.7 +/- 3.3%) were examined before and after 6 weeks of LFES (10 Hz) of the quadriceps and calf muscles of both legs (1 h/day, 7 days/week). Dynamometry was performed weekly to determine maximal muscle strength (F(max); N) and isokinetic peak torque (PT(max); Nm); blood flow velocity (BFV) was measured at baseline and after 6 weeks of LFES using pulsed-wave Doppler velocimetry of the right femoral artery. Six weeks of LFES significantly increased F(max) (from 224.5 +/- 96.8 N to 340.0 +/- 99.4 N; p<0.001), and also PT(max) (from 94.5 +/- 41.5 Nm to 135.3 +/- 28.8 Nm; p<0.01). BFV in the femoral artery increased after 6 weeks from 35.7 +/- 15.4 cm/s to 48.2 +/- 18.1 cm/s (p<0.05); BFV values at rest before and after 6 weeks of LFES did not differ significantly. CONCLUSIONS: LFES may improve muscle strength and blood supply, and could be recommended for the treatment of patients with severe CHF.
Keywords: Ventricular Function, Left; koronární cirkulace; Male; biologické markery; funkce levé komory srdeční; srdeční selhání; Biomarkers; elektrická stimulace; srdce; pevnost ve smyku; chronická nemoc; Muscle, Skeletal; C-reaktivní protein; Electric Stimulation; mužské pohlaví; Chronic Disease; rychlost toku krve; kosterní svaly; lidé; Shear Strength; ženské pohlaví; Heart Failure; Humans; Body Mass Index; Coronary Circulation; index tělesné hmotnosti; C-Reactive Protein; Female; Heart; lidé středního věku; Blood Flow Velocity; Middle Aged